2013
DOI: 10.5267/j.dsl.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance attributes, firm characteristics and the level of corporate disclosure: Evidence from the Indian listed firms

Abstract: This study investigates the association between firm characteristics, corporate governance attributes and the level of corporate disclosure of listed firms in India. The research paper has been based on a sample of 60 firms listed in the Bombay Stock Exchange (BSE) / National Stock Exchange (NSE) during the study period from 2000-01 to 2009-10. The study has used the Standard & Poor (2008) model for measuring the level of corporate disclosure. To examine the association between explanatory variables and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 29 publications
4
42
3
1
Order By: Relevance
“…Profitability and the extent of voluntary disclosure. Empirically, previous studies find a positive association between profitability of the company and the level of voluntary disclosure (Vu, 2012;Nandi & Ghosh, 2013;Zhang, 2013). A company with high profitability tends to enter the voluntary disclosure with the aim to distinguish themselves from companies with low profitability, to increase the stock price, and to mobilize capital more easily.…”
Section: Hypothesis Development the Relation Between Company Charactementioning
confidence: 99%
See 3 more Smart Citations
“…Profitability and the extent of voluntary disclosure. Empirically, previous studies find a positive association between profitability of the company and the level of voluntary disclosure (Vu, 2012;Nandi & Ghosh, 2013;Zhang, 2013). A company with high profitability tends to enter the voluntary disclosure with the aim to distinguish themselves from companies with low profitability, to increase the stock price, and to mobilize capital more easily.…”
Section: Hypothesis Development the Relation Between Company Charactementioning
confidence: 99%
“…To date, there have been several studies of various researchers around the world on the relation between the board independence and the level of voluntary disclosure. Vu (2012), Sukthomya (2011), Alves et al (2012), Nandi and Ghosh (2013), Lan et al (2013), Al-Janadi et al (2013), andQu (2011) revealed that the proportion of independent directors on corporate board is an important aspect associated positively with voluntary disclosure. The hypothesis in this study is proposed as follows:…”
Section: The Relation Between the Corporate Governance And The Extentmentioning
confidence: 99%
See 2 more Smart Citations
“…They also recommended that the unremunerated reserve requirement could influence asset prices, through larger exchange rate volatility and through changes in exposure of firms to exchange rate volatility. Nandi and Ghosh (2013) investigated the association between firm characteristics, corporate governance attributes and the level of corporate disclosure of listed firms in India. The research paper has been based on a sample of 60 companies listed in the Bombay Stock Exchange (BSE) / National Stock Exchange (NSE) during the study period from 2000-01 to 2009-10.…”
Section: Introductionmentioning
confidence: 99%